2009
DOI: 10.1074/jbc.m807285200
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Folding and Ligand-binding Properties of LRP6 β-Propeller Domains

Abstract: Wnt/␤-catenin signaling controls cell growth during development, and its misregulation in adults can cause human diseases. LRP6, the essential co-receptor for the Wnt pathway, consists of four ␤-propeller domains flanked by epidermal growth factor repeats in its extracellular region. To understand the maturation and ligand-binding properties of individual BP domains, we generated soluble receptor consisting of individual BPs, as well as combinations of these domains. We show that BP1, BP2, and BP4 each can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 41 publications
5
31
0
Order By: Relevance
“…Although Wnt3a has been shown to bind to E1E2 in an enzyme-linked immunosorbent assay (35), this experiment was performed with conditioned media containing E1E2, raising questions about whether other proteins are involved in mediating this binding event. The differences seen between the direct binding studies reported here and interaction analyses based either on enzyme-linked immunosorbent assay (35) or indirect transcriptional readouts (9) stress the importance of well defined biochemical assays using purified proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Although Wnt3a has been shown to bind to E1E2 in an enzyme-linked immunosorbent assay (35), this experiment was performed with conditioned media containing E1E2, raising questions about whether other proteins are involved in mediating this binding event. The differences seen between the direct binding studies reported here and interaction analyses based either on enzyme-linked immunosorbent assay (35) or indirect transcriptional readouts (9) stress the importance of well defined biochemical assays using purified proteins.…”
Section: Discussionmentioning
confidence: 99%
“…To rule out the possibility that all-trans-RA, 9-cis-RA, 13-cis-RA, and bexarotene increase apoE levels in the conditioned media by suppressing its cellular clearance, we examined the levels of two major apoE metabolic receptors LDLR and LRP1 (32). We found that receptor expression at both protein and mRNA levels was not changed by tested compounds (Fig.…”
Section: Ra Isomers Increase Apoe Secretion In Primary Culture Ofmentioning
confidence: 99%
“…LRP5/6 collaborate with FZDs through formation of a ternary WNT/FZD/LRP5/6 complex (Tamai et al, 2000;Wehrli et al, 2000). In contrast to FZDs, LRP5/6 do not contain any CRD-WNT binding domains; rather, their N-terminal ␤ propeller epidermal growth factor repeats are essential for the interaction with the WNT/FZD complex (Hey et al, 1998;Liu et al, 2009;Bourhis et al, 2010). In fact, a recent mapping study identified unique binding patterns of different WNTs to the extracellular domains of LRP6, showing that several WNTs, such as WNT-3A and WNT-9B, can bind simultaneously (Bourhis et al, 2010).…”
Section: B Low-density Lipoprotein Receptor-related Protein 5/6mentioning
confidence: 99%